2012
DOI: 10.3109/10799893.2012.692118
|View full text |Cite
|
Sign up to set email alerts
|

Receptor-specific regulation of ERK1/2 activation by members of the “free fatty acid receptor” family

Abstract: The results demonstrate a novel role of Rac in GPCR-mediated ERK1/2 signaling, and that GPCRs belonging to the same family can regulate ERK1/2 activation by different receptor-specific mechanisms.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
35
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(41 citation statements)
references
References 20 publications
4
35
0
Order By: Relevance
“…This study confirmed the relationship between linoleic acid treatment and activation of the ERK-MAP kinase pathway (Fig. 2), consistent with a previous report [21]. The microarray data showed that treatment with linoleic acid resulted in upregulation of transforming growth factor, beta receptor II (Tgfbr2), calcium channel, voltage-dependent, gamma subunit 5 (Cacng5), calcium channel, voltage-dependent, beta 4 subunit (Cacnb4), and protein kinase C, beta (PrkcB), and downregulation of ribosomal protein s6 kinase, 90 kDa, polypeptide 6 (Rps6ka6) and interleukin 1, alpha (Il1α).…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…This study confirmed the relationship between linoleic acid treatment and activation of the ERK-MAP kinase pathway (Fig. 2), consistent with a previous report [21]. The microarray data showed that treatment with linoleic acid resulted in upregulation of transforming growth factor, beta receptor II (Tgfbr2), calcium channel, voltage-dependent, gamma subunit 5 (Cacng5), calcium channel, voltage-dependent, beta 4 subunit (Cacnb4), and protein kinase C, beta (PrkcB), and downregulation of ribosomal protein s6 kinase, 90 kDa, polypeptide 6 (Rps6ka6) and interleukin 1, alpha (Il1α).…”
Section: Discussionsupporting
confidence: 93%
“…Since the involvement of extracellular signal-regulated kinase 1/2 (ERK1/2) in the GPR40-mediated signaling pathway was suggested [6,20], a recent report demonstrated that FFA-mediated ERK1/2 activation was through c-RAF (RAF, a proto-oncogene serine/threonine-protein kinase) and MEK1/2 (ERK kinase) via Rac1 [21]. Although attention was focused on changes in intracellular Ca 2+ , the possible involvement of ERK1/2 in GPR40-mediated insulin secretion remains unclear.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, activation of FFAR1 decreased OA-induced lipid accumulation in HepG2 cells through a p38-dependent pathway. The MAPK pathway is involved in the biological functions of FFAR1 (Seljeset & Siehler 2012). FFAR1 activates ERK-MAPK pathway to control the plasticity of the b-cell mass and improve glycemic control (Zhang et al 2007).…”
Section: Discussionmentioning
confidence: 99%
“…FFAR2 couples to G q and G i pathways, whereas FFAR3 is presumed to couple exclusively to the pertussis toxin-sensitive G i pathway (102,103). Both receptors have also been demonstrated to activate MAPK (103,109), which has been associated with GLP1 release from EEC cell lines in response to a number of stimuli (82,110). SCFA-dependent GLP1 secretion was significantly impaired in Ffar2 knockout mice, which also exhibited reduced circulating GLP1 concentrations, supporting a role for FFAR2 signaling in GLP1 secretion (108,111).…”
Section: Gut Microbiota Host Defense and Eec Signalingmentioning
confidence: 99%